2017
DOI: 10.1038/leu.2017.41
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of regulatory T cells determines the outcome of the T-cell-engaging antibody blinatumomab in patients with B-precursor ALL

Abstract: Blinatumomab can induce a complete haematological remission in patients in 46.6% with relapsed/refractory B-precursor acute lymphoblastic leukemia (r/r ALL) resulting in a survival benefit when compared with chemotherapy. Only bone marrow blast counts before therapy have shown a weak prediction of response. Here we investigated the role of regulatory T cells (Tregs), measured by CD4/CD25/FOXP3 expression, in predicting the outcome of immunotherapy with the CD19-directed bispecific T-cell engager construct blin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
181
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(200 citation statements)
references
References 36 publications
4
181
1
4
Order By: Relevance
“…Both events can be treated with drug interruption, high-dose steroids and some patients may require tocilizumab [78 & ]. Treatment resistance and relapse after blinatumomab correlates with leukemia burden, extramedullary ALL, PD-L1 blast expression [82] and circulating regulatory T cells [83]. The immunological pressure drives CD19À relapses in 10-20% of patients, due to CD19 expression loss or disrupted membrane trafficking [84], selection of preexisting CD19À clones [85] or lineage switch [86], indicating the need to carefully monitor escape variants.…”
Section: Bispecific Antibodies and Derivativesmentioning
confidence: 99%
“…Both events can be treated with drug interruption, high-dose steroids and some patients may require tocilizumab [78 & ]. Treatment resistance and relapse after blinatumomab correlates with leukemia burden, extramedullary ALL, PD-L1 blast expression [82] and circulating regulatory T cells [83]. The immunological pressure drives CD19À relapses in 10-20% of patients, due to CD19 expression loss or disrupted membrane trafficking [84], selection of preexisting CD19À clones [85] or lineage switch [86], indicating the need to carefully monitor escape variants.…”
Section: Bispecific Antibodies and Derivativesmentioning
confidence: 99%
“…The main disadvantage however of this backbone approach is the in situ activation of autologous T cells. Recent analysis suggests unwanted stimulation of immune suppressive Tregs, which also carry the CD3 molecule, leading to therapy resistance particularly in patients with baseline increased Treg numbers [93]. Of note, Treg frequencies are generally increased in MM [16].…”
Section: T Cells Based Approachesmentioning
confidence: 99%
“…Prior studies have suggested that increased marrow disease burden (>50% blasts) [37], multiple previous relapses [28], or relapsed disease after prior alloSCT [36] are all associated with worse response rates to blinatumomab. In addition, higher regulatory T cell counts and elevated lactate dehydrogenase may also predict poor response [59]. To date, analyses of T cell numbers and cytokine kinetics show no correlation to response rate [9].…”
Section: Expert Opinionmentioning
confidence: 99%